THE VALUES OF ARCHIPELAGIC ISLAM IN A. MUSTOFA BISRI’S POETRY - Abdul Wachid B.S.; Herman J. Waluyo; Rachmat Djoko Pradopo; Suyitno Suyitno (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2018)
This study aims to investigate and describe the values of archipelagic Islam in A. Mustofa Bisri’s poetry. Archipelagic Islam contains three narratives at once, namely: politics, nationality, and culture. The main principle is National brotherhood (ukhuwah wathaniyah), Human brotherhood (ukhuwah basyariyah ), and Islamic brotherhood (ukhuwah Islamiyah ). A. Mustofa Bisri is chosen as the subject of this research because besides being a charismatic kiai , he is also a famous poet. A. Mustofa Bisri often voiced the values of humanity, love, compassion, peace and human equality. The results of this study are some principles, namely the principle to establish God as God, treat humans as human beings, and manage nature properly and correctly. The principles constitute the contextualization of the values of archipelagic Islam that was received by A. Mustofa Bisri in his poetry, as well as the prophetic manifestations.